UJI KEPEKAAN BAKTERI Escherichia coli HASIL ISOLASI DARI URIN PASIEN RUMAH SAKIT Dr. Sardjito TERHADAP ANTIBIOTIK GOLONGAN -LAKTAM - Sri harnanik; Sri Mulyaningsih; Asih Triastuti (Universitas Islam Indonesia, 2005)
ABSTRACTUncontrolled use of antibiotic caused the emergence of bacteria strain resistant toward of antibiotic. The sensitivity assay of E. coli toward -lactam antibiotic has been done. The sensitivity assay was started with isolated bacteria from patients urine at Dr. Sardjito hospital followed by count total of colony/number of germ which growth and identified the bacteria. The Kirby Bauer method was performed. Antibiotic impregnated disk (ampicillin 30 g, sulbactam/ampicillin 20 g, cefotaxim 30 g, ceftazidime 30 g, ceftriaxon 30 g, cefpirom 30 g, cefepim 30 g and imipenem 10 g) were placed on agar plate previously streaked with suspension of E. coli (1.10 8 CFU/ml). The plates were incubated for 18-24 hours at 37 0 C. The diameters of the zone inhibition were measured, and compared to standar interpretive zone sizes. The result of the study showed that all of E. coli resistant toward antibiotic ampicillin; 65% resistant toward antibiotic sulbactam/ampicillin; 50% still sensitive toward antibiotic third cefalosporin generation that is cefotaxim, ceftazidime, ceftriaxon; more than 50% sensitive toward fourth cefalosporin generation like cefepim, cefpirom and all of pathogen bacteria E. coli sensitive toward antibiotic imipenem.Key Words : E. coli, -lactam antibiotic, Sensitivity assay, Urine of patient hospital.